A Content Analysis of Four Peer-Reviewed Middle Grades Publications: Are We Really Paying Attention to Every Young Adolescent? - Kathleen Brinegar (Middle Grades Review, 2015)
The field of middle grades education clearly articulates a vision for education focused on supporting the needs and interests of every young adolescent (National Middle School Association, 2010; Jackson & Davis, 2000). This study sought to identify the ways in which recent middle grades research intersects with this vision by utilizing qualitative content analysis (Hsieh & Shannon, 2005) to identify current topics explored in middle grades research over the past 13 years (2000-2013). In total the content of 691 articles and chapters was analyzed from the following publications: Handbook of Research in MiddleLevel Education series, Middle Grades Research Journal (MGRJ), Middle School Journal (MSJ), and Research in Middle Level Education (RMLE) Online . In many ways the body of research examined was diverse in its breadth and depth related to a variety of thematic areas such as curriculum and instruction. However, there is a dearth of published research in areas that are critical to developing systems and practices meant to support the needs of every young adolescent, including specific populations (e.g. males, African Americans, students with disabilities), diversity (e.g., broad topics related to equity, discrimination, social justice, multicultural education), motivation and engagement, student voice, leadership, and family/community connections. Given that these are important publications in the field of middle grades education, the gaps identified within them cannot be ignored if the goal is to provide a positive schooling experience for every young adolescent.